When Bioequivalence in Healthy Volunteers May not Translate to Bioequivalence in Patients: Differential Effects of Increased Gastric pH on the Pharmacokinetics of Levothyroxine Capsules and Tablets - Corinne Seng Yue; Salvatore Benvenga; Claudia Scarsi; Luca Loprete; Murray Ducharme (Frontiers Media S.A., 2015)
Purpose:  Clinical studies have suggested that proton pump inhibitors may decrease levothyroxine absorption and an in vitro study suggested that the effect of pH on dissolution may differ with formulation. To determine the impact of formulation on the pharmacokinetics of levothyroxine in altered gastric pH conditions, this study compared the pharmacokinetics of levothyroxine capsules and tablets, two formulations deemed bioequivalent in healthy volunteers under fasting conditions, when taken with or without esomeprazole. Methods: Two clinical studies were conducted in healthy volunteers given single dose levothyroxine (600 mg) with a 45-day washout period. In Study 1 (parallel-design/two-way crossover), 16 subjects received either levothyroxine capsules or tablets, each group with or without prior administration of intravenous esomeprazole (maximum dose of 80 mg). In Study 2 (two-way crossover), 16 subjects received both capsules or tablets after intravenous esomeprazole. Blood samples were collected pre-dose and up to 24 hours post-dose. Baseline-adjusted pharmacokinetic parameters were calculated: Cmax (maximal concentration), Tmax (time to Cmax), AUC0-t (area under the concentration-time curve from 0 to the last detectable concentration), AUC0-6 and AUC0-12 (areas under the curve from 0 to 6 and 12 hours, respectively). Analyses of variance were conducted to compare ln-transformed Cmax and AUC. Non-parametric Tmax analyses were done. Results: In Study 1, esomeprazole caused a greater decrease in overall levothyroxine exposure of tablets vs. capsules (13% vs 6% for Cmax, 18% vs. 14% for AUC0-6, 17% vs. 5% for AUC0-12 and 10% vs. 8% for AUC0-t). In Study 2 esomeprazole administration resulted in a 16% smaller levothyroxine exposure with tablets vs. capsules. No statistically significant differences in Tmax were found. Conclusions: Although both formulations are considered "bioequivalent" in healthy volunteers, they may not necessarily be bioequivalent in patients with impaired gastric pH conditions. Levothyroxine capsules may therefore be more appropriate for patients with decreased gastric acidity.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.